2015
DOI: 10.1007/s00114-015-1263-x
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effect of a native species on a major plant invader in Europe

Abstract: Biological invasions have become a major global issue in ecosystem conservation. As formalized in the "novel weapon hypothesis", the allelopathic abilities of species are actively involved in invasion success. Here, we assume that allelopathy can also increase the biotic resistance of native species against invasion. We tested this hypothesis by studying the impact of the native species Sambucus ebulus on the colonization of propagules of the invasive species Fallopiaxbohemica and the subsequent development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Denser communities thus should leave less resources and space for potential invaders (Dostál 2011;Dukes 2002;Michelan et al 2013). Furthermore, a high degree of canopy closure in dense communities may also effectively inhibit seed germination, and seedling and juvenile plant growth of invasive exotic species (Christina et al 2015;Emery and Gross 2007;Liao et al 2015;Pearson et al 2018). This is also supported by the fact that undisturbed communities with a closed canopy are less likely to be invaded by exotic plants compared to frequently disturbed communities with an open canopy (Arroyo et al 2018;Davis et al 2000;Sun et al 2015;Tan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Denser communities thus should leave less resources and space for potential invaders (Dostál 2011;Dukes 2002;Michelan et al 2013). Furthermore, a high degree of canopy closure in dense communities may also effectively inhibit seed germination, and seedling and juvenile plant growth of invasive exotic species (Christina et al 2015;Emery and Gross 2007;Liao et al 2015;Pearson et al 2018). This is also supported by the fact that undisturbed communities with a closed canopy are less likely to be invaded by exotic plants compared to frequently disturbed communities with an open canopy (Arroyo et al 2018;Davis et al 2000;Sun et al 2015;Tan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some invasives lack effective natural enemies in their exotic range due to anti-microbial or anti-herbivory properties (Hinz and Schwarzlaender 2004;Cappuccino and Carpenter 2005). Further, most invasives use allelopathy to inhibit growth of adjacent native plants (Callaway et al 2008), and develop monospecific patches (Christina et al 2015). Allelopathy is an effect of one plant species on seeds germination, growth, and development of another adjacent plants by the release of allelochemicals into the environment (Callaway et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The natives or naturalised are preferred over invasive plants because the former have co-evolved with the allelochemicals of the wider ecological community (Zhao et al 2008), and their non-target impacts are likely to be less severe compared to allelopathic traits of invasive species. Conversely, because exotic invasive plants have not co-evolved with native species, they could release allelochemicals which suppress the growth of natives (Christina et al 2015). Thus, if the allelopathic traits of certain invasive are used to control other invasive plants, it might kill adjacent native plants and be deleterious to the wider flora (Zhao et al 2008;Christina et al 2015; Ming Chen and Lin Peng 2018).…”
Section: Introductionmentioning
confidence: 99%
“…elderberry (Sambucus ebulus) have also been reported (Christina et al 2015). It has recently been demonstrated that S. ebulus restrict the colonization and subsequent development of Fallopia x bohemica (Christina et al 2015). Phytochemical analysis on aqueous extracts of eucalyptus and elderberry leaves demonstrate the high relatively amounts of phenolic compounds and antioxidant potential in these plants (see Results section).…”
Section: Introductionmentioning
confidence: 95%
“…In addition to eucalyptus, the phytotoxicity effects of other plants e.g. elderberry (Sambucus ebulus) have also been reported (Christina et al 2015). It has recently been demonstrated that S. ebulus restrict the colonization and subsequent development of Fallopia x bohemica (Christina et al 2015).…”
Section: Introductionmentioning
confidence: 99%